Research on Photogrammetric Processing Methods for Unmanned Aerial Vehicle Imagery in Antarctica - L. Hu; Y. Duan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
Antarctica, abundant in resources and of exceptional scientific value, is a focus of research. Unmanned aerial vehicle (UAV) photogrammetry, as a low-cost and efficient method for geographic information acquisition, plays an important role in Antarctic studies. However, due to the unique conditions of Antarctica, conventional UAV photogrammetry processing methods are inadequate, and relevant research in this area is limited. This paper uses a photogrammetric coordinate system for the Antarctic environment and derives the conversion formulas between geodetic coordinates and the coordinates. This paper also discusses methods for image matching to accelerate image retrieval speed and improve retrieval efficiency in the harsh natural conditions in Antarctica. The results of photogrammetric production using real data confirm that the proposed planar coordinate system is suitable for Antarctic image processing, and the proposed retrieval method effectively addresses the challenges in Antarctic image matching. This provides valuable insights for UAV photogrammetry research in Antarctica.